Interactions in multi-pattern Müllerian communities support origins of new patterns, false structures, imperfect resemblance and mimetic sexual dimorphism - Motyka, Michal; Bocek, Matej; Kusy, Dominik; Bocak, Ladislav (Scientific reports, 2020)
Mimicry is a hot spot of evolutionary research, but de novo origins of aposematic patterns, the persistence of multiple patterns in Müllerian communities, and the persistence of imperfect mimics still need to be investigated. Local mimetic assemblages can contain up to a hundred of species, their structure can be a result of multiple dispersal events, and the gradual build-up of the communities. Here, we investigate the structure of lowland and mountain mimetic communities of net-winged beetles by sampling the Crocker Range in north-eastern Borneo and neighbouring regions. The local endemics evolved from the Bornean lowland fauna which is highly endemic at the species level. We inferred that metriorrhynchine net-winged beetles evolved in high elevations yellow/black and reticulate aposematic high-contrast signals from a widespread low-contrast brown/black pattern. As the mountain range is ~ 6 million years old, and these patterns do not occur elsewhere, we assume their in situ origins. We demonstrate that a signal with increased internal contrast can evolve de novo in a mimetic community and can persist despite its low frequency. Additionally, a similar aposematic signal evolves from different structures and its similarity is imperfect. The community with multiple patterns sets conditions for the evolution of aposematic sexual dimorphism as demonstrated by the yellow/black male and reticulate female pattern of Micronychus pardus. These insights elucidate the complex character of the evolution of mimetic signalling in the dynamically diversifying biota of high tropical mountains.
Keywords: brouci; Wings, Animal; Animal Distribution; Male; mimikry; Color; Sex Characteristics; křídla zvířecí; biologická evoluce; mužské pohlaví; pohlavní dimorfismus; rozšíření zvířat; Biological Mimicry; Animals; ženské pohlaví; Biological Evolution; zvířata; barva; Coleoptera; Borneo; Female